PENDAMPINGAN PEMBUATAN WEBLOG DALAM UPAYA MENINGKATKAN LITERASI BERBASIS KOMPUTER (STUDI KASUS SANTRIWATI PMDG PUTRI KAMPUS 2) - Andi Triyawan; Zulfa Nisa Ul Haq; Atika Rismayasari; Bella Soviatunnisa; Angelia Islamiati Tolo (Universitas Darussalam Gontor, 2021)
This article is an adaptation of the evaluation results of an innovative approach realized in the students of PMDG Putri Kampus 2 who have not used blogs at all. Blog as an interactive and efficient homepage to be managed allows students to be trained in computer-based literacy improvement. With the survey conducted on 28 students of grade 5 KMI or Kulliyatul Mu'allimat Islamiah, it will present different perceptions of each individual. The santriwati who responded to the distribution of the survey form were students who actively participated in the Introduction and Creating Weblog Training. The training was held to measure how much blogs play a role in the students' ability to improve literacy skills.